PENGARUH LATIHAN RANGE OF MOTION (ROM) AKTIF TERHADAP PERUBAHAN RENTANG GERAK SENDI PADA PENDERITA STROKE DI KECAMATAN TANGGUL KABUPATEN JEMBER - Murtaqib Murtaqib (Fakultas Kesehatan Masyarakat, Universitas Jember, 2013)
Stroke the most common cause of disability in the world. The most complication in patients after their got stroke is contracture. Range of motion (ROM) exercise is one of stroke rehabilitation program. This study uses experimental research. The research designs used in this study were experiment with this type of design two group pretest-posttest. In this study conducted active ROM exercises of the different samples. Analysis of data to determine the differences in ROM exercises to increase range of motion in stroke patients is by using ANOVA test with confidence level is 95% (α = 0.05). The results are there differences in range of motion in flexion and extension passive ROM and active ROM in Tanggul Community Health Center Jember, with p value = 0.001 (p < 0.05). The results of the analysis of the difference obtained before the measurement range of flexion at 125.27 degrees and extension difference of 28.27 and analysis of the difference obtained after the measurement range of flexion at 136.67 degrees and extension difference of 8.47. ROM active exercise can be used to improve the range of elbow joint motion of patients with stroke by increased the movement of joint. The research recommend on the needs of further research and the use of this exercise as one of the independent nursing interventions in providing care to stroke patients with contracture. Keywords: flexion, extension, range of motion (ROM)